A phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material and its preparation method and application
By phosphorylation and combining with modified molybdenum disulfide and polyethyleneimine to form a stable cellulose-molybdenum disulfide hydrogel, the problems of insufficient adsorption performance of cellulose-molybdenum disulfide aerogel materials and unstable molybdenum disulfide fixation in the prior art are solved, and the preparation of highly efficient adsorption and environmentally friendly cellulose-molybdenum disulfide aerogel materials are achieved.
Patent Information
- Application Number
- CN202310448311.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-23
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-04-23
AI Technical Summary
In the prior art, the adsorption performance of cellulose-molybdenum disulfide aerogel materials is weak, the molybdenum disulfide fixation is unstable, and the crosslinking agent is not environmentally friendly, which limits its application in dye wastewater treatment.
The phosphorylated microcrystalline cellulose is dissolved using ionic liquid and doped with modified molybdenum disulfide on it. The cellulose-molybdenum disulfide hydrogel is formed by cross-linking of polyethyleneimine to achieve stable immobilization of molybdenum disulfide, and finally the phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material is prepared by freeze-drying.
The adsorption capacity of aerogel materials is improved and the stable immobilization of molybdenum disulfide is achieved. The material is green and environmentally friendly and recyclable, and has a significant adsorption effect in dye wastewater.
Smart Images

Figure CN116253922B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aerogel material synthesis, and more specifically to a phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material and a preparation method and application thereof. Background Art
[0002] With the rapid development of the dye industry, the discharge of dye wastewater is increasing. Dye wastewater has the characteristics of high chromaticity, high toxicity, and difficulty in degradation. Discharging it into the environment will reduce the transparency of the water body and have a huge impact on the aquatic ecosystem and the surrounding environment. At the same time, the large amount of toxic substances contained in the dye wastewater will endanger human health. Therefore, in order to protect the ecosystem and human health, how to quickly and efficiently remove harmful substances in dye wastewater is an urgent problem to be solved, which has important theoretical and social significance. At present, the treatment methods for dye wastewater mainly include adsorption, biodegradation, photocatalysis, advanced oxidation, etc. Among them, the adsorption method has the characteristics of simple operation, low cost, high efficiency, environmental protection, recyclability, and economical and practical, and is widely used in dye wastewater. Cellulose is widely used in the field of adsorption due to its advantages such as renewability and easy degradation. Cellulose can be used to adsorb pollutants by preparing gel materials, but there is a problem of low adsorption capacity.
[0003] Molybdenum disulfide (MoS2) is a two-dimensional transition metal disulfide (TMD) with a S-Mo-S sandwich structure. The layers are connected by weak van der Waals forces. It has a large surface area, strong adsorption performance and high stability. Therefore, it has a good application prospect in environmental adsorption. However, MoS2 nanopowder is difficult to recycle in water treatment. Therefore, how to achieve the immobilization of MoS2 has become a difficult problem.
[0004] The prior art discloses a method for preparing a cross-linked cellulose@molybdenum disulfide aerogel composite adsorbent, using cross-linked cellulose aerogel as a carrier, and directly doping molybdenum disulfide nanoparticles into a cellulose suspension by a method of premixing-crosslinking fixation-freezing pores, and then adding a crosslinking agent to form a three-dimensional network structure of cellulose to fix the molybdenum disulfide particles. In the prior art, cellulose is dissolved by using a NaOH / H2O / urea system, and it is combined with molybdenum disulfide to prepare an aerogel material to achieve the immobilization of molybdenum disulfide. However, the NaOH / H2O / urea system in this technology affects the stability of molybdenum disulfide fixation, and the crosslinking agent epichlorohydrin used is volatile and harmful to the environment. In addition, the low temperature operating conditions and strong alkaline environment of the prior art limit its further application.
[0005] Therefore, there is an urgent need to develop an environmentally friendly and simple method for preparing cellulose-molybdenum disulfide aerogel materials, which can stably fix molybdenum disulfide on cellulose and prepare cellulose-molybdenum disulfide aerogel materials with high adsorption capacity, green and environmental protection, and recyclability. Summary of the invention
[0006] The primary purpose of the present invention is to overcome the shortcomings of the prior art, such as the weak adsorption performance of cellulose-molybdenum disulfide aerogel materials, the unstable fixation of molybdenum disulfide, and the environmentally unfriendly crosslinking agent, and provide a method for preparing phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel materials. The preparation method uses ionic liquid (IL) to dissolve phosphorylated microcrystalline cellulose, and on this basis, dopes modified molybdenum disulfide; forms cellulose-molybdenum disulfide hydrogel through the crosslinking effect of polyethyleneimine, realizes the stable fixation of molybdenum disulfide, and finally prepares phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel materials through freeze drying.
[0007] A further object of the present invention is to provide a phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material prepared by the above method, which is beneficial to the adsorption of organic matter in dye wastewater and has the characteristics of high adsorption capacity, green environmental protection, and recyclability.
[0008] The third object of the present invention is to provide an application of the above-mentioned phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material in the adsorption of dye wastewater.
[0009] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0010] A method for preparing a phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material comprises the following steps:
[0011] S1. adding phosphorylated cellulose and molybdenum disulfide nanosheets to an ionic liquid and mixing to obtain a mixture;
[0012] S2. Add cross-linking agent polyethyleneimine to react to obtain hydrogel, remove impurities and freeze-dry to obtain phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material.
[0013] The present invention utilizes ionic liquid to dissolve phosphorylated microcrystalline cellulose, on this basis, dopes molybdenum disulfide nanosheets, ultrasonically stirs, and mixes evenly. The ionic liquid can dissolve the phosphorylated cellulose without destroying the structure of the molybdenum disulfide nanosheets in the system. Polyethyleneimine is added to the obtained mixed solution and continues to stir and react, and then the mixed solution is solidified and regenerated to prepare a hydrogel, and impurities in the hydrogel are removed by soaking with deionized water, and freeze-dried to obtain a phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material. Polyethyleneimine (PEI) is a biocompatible high molecular polymer with high reactivity. The molecule contains a large number of primary amines, secondary amines and tertiary amine groups, which is beneficial to improving the hydrophilicity and adsorption capacity of the material. It can also form an intricate gel network as a cross-linking agent to improve the stability of the material. Polyethyleneimine can not only combine with the phosphate group of phosphorylated cellulose through acid-base action, but also combine with molybdenum disulfide nanosheets through the action of electrostatic self-assembly, so that the molybdenum disulfide nanosheets are uniformly dispersed in the phosphorylated cellulose solution, reducing the precipitation of molybdenum disulfide and the agglomeration between particles, improving the stability and hydrophilicity of molybdenum disulfide, achieving stable immobilization of molybdenum disulfide, improving the anti-swelling performance of the hydrogel, and the aerogel material obtained after freeze-drying is loose and porous, which is conducive to the adsorption of pollutants. The present invention uses polyethyleneimine to replace the cross-linking agent epichlorohydrin, which is volatile and harmful to the environment, and epichlorohydrin only plays the cross-linking role of the cross-linking agent in the aerogel material, while polyethyleneimine can also introduce amino groups that are beneficial to adsorption, improve the adsorption performance of the aerogel material, and reflect the multifunctionality of polyethyleneimine as a cross-linking agent.
[0014] The phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material prepared by the above method of the present invention is beneficial to the adsorption of organic matter in dye wastewater, has the characteristics of high adsorption capacity, green environmental protection, and recyclability, and can adjust the shape according to different working conditions, and has good environmental adaptability.
[0015] Furthermore, the mass content of phosphorylated cellulose in the mixture in step S1 is 2-5%.
[0016] When the amount of phosphorylated cellulose added is too little, the cellulose molecular chains in the solution do not entangle, and the strength of the prepared gel is weak; when the amount of phosphorylated cellulose added is too much, the viscosity of the gel system is high, which is not conducive to the dispersion and cross-linking of molybdenum disulfide nanosheets.
[0017] Furthermore, the mass ratio of phosphorylated cellulose, molybdenum disulfide nanosheets and polyethyleneimine is (1-3): (1-2): (2-4).
[0018] When the amount of molybdenum disulfide nanosheets added is too small, their unit content in the aerogel material is small and the mechanical properties of the aerogel material are weak; when the amount of molybdenum disulfide nanosheets added is too large, it is difficult to disperse in the system and agglomeration between particles occurs.
[0019] When the amount of polyethyleneimine added is too small, the gel network formed is not strong and has an impact on the immobilization of molybdenum disulfide; when the amount of polyethyleneimine added is large, due to the large molecular weight of polyethyleneimine, it will occupy a certain spatial position and there will be a steric hindrance problem.
[0020] Preferably, the mass ratio of phosphorylated cellulose, molybdenum disulfide nanosheets and polyethyleneimine is 2:(1-1.5):(2-3.5).
[0021] Under this ratio, molybdenum disulfide nanosheets can be evenly dispersed in the solution of phosphorylated cellulose, and after adding polyethyleneimine for cross-linking, the entire system forms a stable gel network, and there is no problem of steric hindrance between the three.
[0022] Furthermore, the ionic liquid in step S1 includes one of 1-allyl-3-methylimidazolium chloride and 1-butyl-3-methylimidazolium chloride.
[0023] Ionic liquids are ionic systems that are liquid at room temperature. They have a certain solubility for cellulose and are environmentally friendly and can be recycled. They are ideal solvents for dissolving cellulose. 1-Allyl-3-methylimidazolium chloride and 1-butyl-3-methylimidazolium chloride can effectively dissolve cellulose and cause less damage to the structure of cellulose.
[0024] Preferably, the ionic liquid is 1-allyl-3-methylimidazolium chloride.
[0025] The temperature required for 1-allyl-3-methylimidazolium chloride ionic liquid to dissolve phosphorylated cellulose is lower than that of 1-butyl-3-methylimidazolium chloride, and it causes less damage to the structure of phosphorylated cellulose. In addition, the viscosity of 1-allyl-3-methylimidazolium chloride ionic liquid is low, which is conducive to the dispersion of molybdenum disulfide nanosheets in the ionic liquid system.
[0026] Furthermore, the phosphorylated cellulose in step S1 is prepared by the following method: microcrystalline cellulose is reacted in a phosphorus oxychloride / triethylamine system at 40-50° C. for 5-8 hours, washed, and dried to obtain phosphorylated cellulose.
[0027] After microcrystalline cellulose is modified by phosphorylation, the hydrogen bonding between the molecular chains is weakened, the hydrophilicity is improved, and the introduced phosphate groups are conducive to cross-linking with polyethyleneimine.
[0028] Specifically, at room temperature, a three-necked round-bottom flask is fixed in an oil bath, nitrogen is introduced to maintain an N2 environment, microcrystalline cellulose (MCC) powder is mixed with tetrahydrofuran (THF) and added to the flask, and then phosphorus oxychloride (POCl3) solution is added to the mixed solution, and the stirring device is started. The tetrahydrofuran solvent in which triethylamine (TEA) is dissolved is slowly dripped into the flask using a constant pressure funnel. At this time, a large amount of white smoke emerges from the bottle. After rapid stirring for 30 minutes, the temperature is raised to 40-50°C, and the reaction is continued for 5-8 hours before the stirring is terminated. A vacuum pump filter is used for solid-liquid separation, and the obtained solid is washed with deionized water, and the phosphorylated cellulose is obtained after drying.
[0029] Specifically, in the above method for preparing phosphorylated cellulose, the molar ratio of phosphorus oxychloride to triethylamine is 1:3.
[0030] Preferably, the reaction time of the above method for preparing phosphorylated cellulose is 5 to 6 hours.
[0031] Furthermore, the preparation method of molybdenum disulfide nanosheets in step S1 is as follows: ammonium paramolybdate, thiourea and surfactant are uniformly mixed in a mass ratio of (5-10): (2.5-5): 1, reacted at 200-240° C. for 20-24 hours, and molybdenum disulfide nanosheets are obtained after impurity removal and drying.
[0032] Molybdenum disulfide nanosheets are prepared by a hydrothermal method, and the preparation process is simple. During the preparation process, the surfactant modifies the molybdenum disulfide, opens the interlayer spacing of the molybdenum disulfide, improves the dispersion performance of the molybdenum disulfide in the solution, and is beneficial to the immobilization of the molybdenum disulfide in the gel material.
[0033] Specifically, ammonium paramolybdate, thiourea and a surfactant are dispersed in deionized water at a mass ratio of (5-10): (2.5-5): 1, ultrasonically stirred, and the resulting mixture is transferred to a hydrothermal reactor after being evenly mixed. A hydrothermal reaction is carried out at 200-240° C. for 20-24 hours. After separation, washing with ethanol and deionized water, and freeze-drying, molybdenum disulfide nanosheets are obtained.
[0034] In a specific embodiment, the mass ratio of ammonium paramolybdate, thiourea and surfactant in the above preparation method is 5:2.5:1.
[0035] Furthermore, the surfactant for preparing the molybdenum disulfide nanosheets includes one of polyvinyl pyrrolidone (PVP) and cetyltrimethylammonium bromide (CTAB).
[0036] Preferably, the surfactant is polyvinyl pyrrolidone.
[0037] Specifically, the temperature condition of step S1 is 70-80°C.
[0038] If the mixing temperature is too low, the ionic liquid cannot dissolve the phosphorylated cellulose, and if the mixing temperature is too high, the structure of the phosphorylated cellulose will be destroyed.
[0039] Specifically, the reaction time of step S1 is 1 h.
[0040] Specifically, the reaction temperature of step S2 is 50° C. and the reaction time is 1 h.
[0041] The present invention also protects a phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material prepared by the method.
[0042] The present invention also protects the application of the phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material in the adsorption of dye wastewater.
[0043] Preferably, the dye wastewater is methyl orange wastewater.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] (1) The method for preparing the phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material of the present invention modifies the microcrystalline cellulose, thereby weakening the hydrogen bonding between its molecular chains and improving its hydrophilic properties, and the introduced phosphate groups are beneficial to cross-linking with polyethyleneimine; the modification of molybdenum disulfide by the present invention opens up the interlayer spacing of molybdenum disulfide, improves the dispersion performance of molybdenum disulfide in the solution, and is beneficial to the immobilization of molybdenum disulfide in the gel material.
[0046] (2) In the preparation method of the phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material of the present invention, polyethyleneimine can not only combine with the phosphate group of phosphorylated cellulose through acid-base action, but also combine with molybdenum disulfide nanosheets through the action of electrostatic self-assembly, so that the molybdenum disulfide nanosheets are uniformly dispersed in the phosphorylated cellulose solution, reducing the precipitation of molybdenum disulfide and the agglomeration between particles, improving the stability and hydrophilicity of molybdenum disulfide, achieving stable immobilization of molybdenum disulfide, improving the anti-swelling performance of the hydrogel, and the aerogel material obtained after freeze-drying is loose and porous, which is conducive to the adsorption of pollutants. The present invention uses polyethyleneimine to replace the cross-linking agent epichlorohydrin, which is volatile and harmful to the environment, and epichlorohydrin only plays the cross-linking role of the cross-linking agent in the aerogel material, while polyethyleneimine can also introduce amino groups that are beneficial to adsorption, improve the adsorption performance of the aerogel material, and reflect the multifunctionality of polyethyleneimine as a cross-linking agent.
[0047] (3) The phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material prepared by the present invention has an excellent adsorption effect on methyl orange (MO) wastewater, and the adsorption amount can reach more than 429 mg / g.
[0048] (4) The phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material prepared by the present invention achieves stable immobilization of molybdenum disulfide and still has good adsorption performance for 100 mg / L methyl orange wastewater after four cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 The infrared spectra (FTIR) of microcrystalline cellulose (MCC), phosphorylated cellulose (PMCC) and phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel materials (PEI-PMCC / MoS2).
[0050] Figure 2 The figures are effect diagrams of material molding tests on the hydrogel obtained in step S2 of Example 1 and the mixture B obtained in step S2 of Comparative Example 2; wherein (a) and (b) are the hydrogels obtained in step S2 of Example 1, and (c) and (d) are the mixture B obtained in step S2 of Comparative Example 2.
[0051] Figure 3 The figures are effect diagrams of the shape diversity test of the hydrogels obtained in step S2 of Example 1; wherein (a) is hydrogel A, (b) is hydrogel B, and (c) is hydrogel C.
[0052] Figure 4 This is a graph showing the adsorption data of methyl orange by the phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material prepared in Example 1 and the composite aerogel material prepared in Comparative Example 1 under different initial concentrations.
[0053] Figure 5 This is a graph of the recycling adsorption data of the phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material prepared in Example 1. DETAILED DESCRIPTION
[0054] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.
[0055] The experimental methods in the following examples without specifying specific conditions are generally carried out according to conventional conditions in the art or conditions recommended by the manufacturer; the raw materials, reagents, etc. used are all available from the conventional market unless otherwise specified.
[0056] Example 1
[0057] A method for preparing a phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material comprises the following steps:
[0058] S1. 0.20 g of phosphorylated cellulose and 0.13 g of molybdenum disulfide nanosheets were added to 8 g of ionic liquid 1-allyl-3-methylimidazolium chloride, and reacted at 75° C. for 1 h, and mixed to obtain a mixture;
[0059] S2. Add 0.22g of cross-linking agent polyethyleneimine to react at 50°C for 1h to obtain a hydrogel, remove impurities and freeze-dry to obtain phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material (PEI-PMCC / MoS2),
[0060] The mass content of phosphorylated cellulose in the mixture in step S1 is 2.4%,
[0061] The mass ratio of the phosphorylated cellulose, molybdenum disulfide nanosheets and polyethyleneimine is 2:1.3:2.2.
[0062] The preparation method of phosphorylated cellulose is as follows:
[0063] Under normal temperature conditions, a three-necked round-bottom flask is fixed in an oil bath, nitrogen is introduced to maintain an N2 environment, 1.0-3.0 g of microcrystalline cellulose (MCC) powder is mixed with tetrahydrofuran (THF) and added to the flask, and then 0.06-0.20 mol of phosphorus oxychloride (POCl3) solution is added to the mixed solution, and the stirring device is started. Use a constant pressure funnel to slowly drip 0.18-0.60 mol of triethylamine (TEA) in tetrahydrofuran solvent into the flask, at which time a large amount of white smoke emerges from the bottle, and the temperature is raised to 40-50°C after rapid stirring for 30 minutes, and the stirring is terminated after the reaction is continued for 5-8 hours. Use a vacuum pump filter to separate the solid and liquid, wash the obtained solid with deionized water, and dry it to obtain phosphorylated cellulose.
[0064] The preparation method of molybdenum disulfide nanosheets is as follows:
[0065] Ammonium paramolybdate, thiourea and surfactant were dispersed in deionized water in a mass ratio of 5:2.5:1, ultrasonically stirred, and the obtained mixture was transferred to a hydrothermal reactor after being evenly mixed. The mixture was subjected to a hydrothermal reaction at 200°C for 20 hours. Molybdenum disulfide nanosheets were obtained after separation, washing with ethanol and deionized water, and freeze-drying.
[0066] Example 2
[0067] A method for preparing a phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material is basically the same as Example 1, except that the mass ratio of phosphorylated cellulose, molybdenum disulfide nanosheets and polyethyleneimine is 2:1.5:2.5.
[0068] Example 3
[0069] A method for preparing a phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material is basically the same as Example 1, except that the mass ratio of phosphorylated cellulose, molybdenum disulfide nanosheets and polyethyleneimine is 2:1.5:3.5.
[0070] Example 4
[0071] A method for preparing a phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material is basically the same as Example 1, except that the mass ratio of phosphorylated cellulose, molybdenum disulfide nanosheets and polyethyleneimine is 2:1.5:4.2.
[0072] Comparative Example 1
[0073] This comparative example provides a microcrystalline cellulose aerogel material (PEI-PMCC), and the preparation process thereof is consistent with Example 1 except that molybdenum disulfide is not added.
[0074] Comparative Example 2
[0075] A method for preparing a composite aerogel material comprises the following steps:
[0076] S1. 0.20 g of phosphorylated cellulose and 0.13 g of molybdenum disulfide nanosheets were added to 8 g of a sodium hydroxide / urea mixed solution to obtain a mixture A;
[0077] S2. Add 0.22 g of cross-linking agent polyethyleneimine and react at 50° C. for 1 h to obtain mixture B.
[0078] The following experiments and tests were conducted on the aerogel materials prepared in the embodiments and comparative examples.
[0079] (1) Material characterization test
[0080] Material characterization tests were performed on microcrystalline cellulose (MCC), phosphorylated cellulose (PMCC) and phosphorylated microcrystalline cellulose-modified molybdenum disulfide (PEI-PMCC / MoS2) prepared in Example 1.
[0081] The testing method is as follows: the infrared spectra of microcrystalline cellulose, phosphorylated cellulose and phosphorylated microcrystalline cellulose-modified molybdenum disulfide prepared in Example 1 are measured using a Thermo Scientific iN10 Fourier transform infrared spectrometer.
[0082] Test results such as Figure 1 As shown in the figure, after phosphorylation, the FTIR spectrum of PMCC shows that 804cm -1 and 1260cm -1The (COP) and (P=O) functional groups appeared at 565 cm -1 The (Mo-S) attributable to molybdenum disulfide indicated that MoS2 was successfully loaded onto phosphorylated microcrystalline cellulose, while the 2848 cm -1 (CH), 1565cm -1 (-NH), 1420cm -1 (CN), and 1309cm -1 (NH) is polyethyleneimine (PEI) in the material, indicating that after a series of reactions, PEI is successfully loaded onto the aerogel material to obtain phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material.
[0083] (2) Material forming test
[0084] The hydrogel obtained in step S2 of Example 1 and the mixture B obtained in step S2 of Comparative Example 2 were subjected to a material molding test.
[0085] The test method is as follows: 1) pour the mixture obtained in step S2 of Example 1 into a 5 mL small beaker, let it stand to form, leave it at room temperature overnight and then invert it;
[0086] 2) Pour the mixture B obtained in step S2 of comparative example 2 into a 5 mL small beaker, let it stand, and then invert it at room temperature overnight.
[0087] The test results are as follows Figure 2 As shown, from Figure 2 As can be seen from (a) and (b), the hydrogel obtained in step S2 of Example 1 has no fluidity in the small beaker and has a certain gel shape. After the hydrogel is immersed in deionized water to remove the ionic liquid, it still maintains a stable three-dimensional network structure, indicating that the phosphorylated microcrystalline cellulose is dissolved by ionic liquid, and on this basis, molybdenum disulfide nanosheets are doped, and a three-dimensional structured hybrid hydrogel material can be prepared under the cross-linking effect of polyethyleneimine. Figure 2 As can be seen from (c) and (d), after the mixture B obtained in step S2 of comparative example 2 was inverted after standing overnight, the mixture still appeared liquid, indicating that adding the crosslinking agent polyethyleneimine to the alkaline urine system could not form a hydrogel.
[0088] (3) Shape diversity test
[0089] The hydrogel obtained in step S2 of Example 1 was subjected to a shape diversity test.
[0090] The test method is as follows: 1) pouring the obtained mixture into a 5 mL small beaker and letting it stand to form a columnar gel (hydrogel A);
[0091] 2) The obtained mixture was evenly applied to a glass plate, and after standing overnight, it was solidified and regenerated with deionized water to obtain a film (hydrogel B);
[0092] 3) The obtained mixture was injected into deionized water with a syringe for coagulation and regeneration to obtain a microspherical gel (hydrogel C).
[0093] The test results are as follows Figure 3 As shown, after the hydrogels A, B, and C were immersed in deionized water to remove impurities, it was found that the three gel materials with different shapes could all maintain their good shape structures, indicating that the phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material provided by the present invention has a variety of shapes, can be adjusted accordingly according to different working conditions, and has good environmental adaptability.
[0094] (4) Adsorption test
[0095] The aerogel materials prepared in Examples 1 to 4 and Comparative Example 1 were subjected to adsorption tests.
[0096] The test method is as follows: 100 mg / L methyl orange solution is used as the test solution, and the pH of the wastewater is adjusted to 7. 30 mL of simulated wastewater is accurately transferred into a centrifuge tube with a pipette, and 10 mg of adsorbent is added. Then it is placed in a water bath oscillator, the temperature is set to 303K, the oscillation frequency is set to 180 r / min, and it is taken out after 16 hours of oscillation, and the test solution is filtered with a 0.45 μm filter membrane. The remaining MO concentration in the solution is measured using a UV spectrophotometer and its adsorption amount is calculated.
[0097] The test results are as follows: the adsorption amounts of the phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel materials prepared in Examples 1 to 4 are 250 mg / g, 245 mg / g, 251 mg / g, and 242 mg / g, respectively, and the adsorption amount of the composite aerogel material prepared in Comparative Example 1 is 201 mg / g. By comparing the test results of Example 1 and Comparative Example 1, it can be seen that polyethyleneimine interweaves the phosphorylated cellulose and the molybdenum disulfide nanosheets to form a stable gel network, realizes the stable immobilization of molybdenum disulfide, and improves the adsorption performance of the aerogel material, and the adsorption performance is enhanced by about 25%. By comparing the test results of Examples 1 to 4, it can be seen that increasing the amount of cross-linking agent polyethyleneimine can improve the adsorption performance of the aerogel material, but when the amount is too much, the adsorption amount of the aerogel material decreases.
[0098] (5) Adsorption test at different concentrations
[0099] The phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material prepared in Example 1 and the microcrystalline cellulose aerogel material prepared in Comparative Example 1 were subjected to adsorption tests at different concentrations.
[0100] The test method is as follows: the concentration of methyl orange (MO) configured in the test experiment is 50-400 mg / L, and the pH of the wastewater is adjusted to 7. Use a pipette to accurately transfer 30 mL of MO wastewater into a centrifuge tube and add 10 mg of adsorbent. Then put it into a water bath oscillator, set the oscillation frequency to 180 r / min, the temperature to 303 K, take it out after oscillating for 16 hours, and filter the test solution with a 0.45 μm filter membrane. After diluting it a certain number of times, use a UV spectrophotometer to measure the remaining MO concentration in the solution and calculate its adsorption amount.
[0101] Test results such as Figure 4 As shown in the figure, it can be seen that the adsorption amount of methyl orange by the phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material can reach up to 429 mg / g, which is much higher than the adsorption amount of the microcrystalline cellulose aerogel material in comparative example 1, indicating that the phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material has a strong adsorption capacity for methyl orange (MO) dye wastewater.
[0102] (6) Recycling test
[0103] The phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material prepared in Example 1 was tested for recycling.
[0104] The test method is as follows: 100 mg / L methyl orange solution is used as the experimental solution, and the pH of the wastewater is adjusted to 7. Use a pipette to accurately transfer 30 mL of simulated wastewater into a centrifuge tube and add 10 mg of adsorbent. Then put it into a water bath oscillator, set the temperature to 303K, the oscillation frequency to 180 r / min, take it out after 16 hours of oscillation, and filter the test liquid with a 0.45 μm filter membrane. The obtained test liquid is recorded as the first recycling. Subsequently, the adsorbent is separated from the waste liquid, and is successively immersed in an alkaline solution and deionized water for analysis. After freeze-drying, the next round of adsorption is carried out. This experiment examines the adsorption performance of the adsorbent for methyl orange solution after 4 rounds of recycling.
[0105] Test results such as Figure 5As shown in the figure, the methyl orange adsorption capacity before recycling was 250 mg / g. After four rounds of recycling tests, the methyl orange adsorption capacity was 234 mg / g, 202 mg / g, 182 mg / g and 178 mg / g respectively. The phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material still has good adsorption performance for methyl orange solution. This shows that the structure of the aerogel material remains stable during the cyclic adsorption process, the functional groups of the material are less damaged, and the effective fixation of molybdenum disulfide in the aerogel is achieved.
[0106] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. Those skilled in the art should understand that other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material, characterized in that: The following steps are involved: S1. adding phosphorylated cellulose and molybdenum disulfide nanosheets to an ionic liquid and mixing to obtain a mixture; S2. adding a cross-linking agent, polyethyleneimine, to react and obtain a hydrogel, and then freeze-drying to obtain a phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material after removing impurities; Wherein, the phosphorylated cellulose in step S1 is prepared by the following method: The microcrystalline cellulose is reacted in a phosphorus oxychloride / triethylamine system at 40-50°C for 5-8 hours, washed, and dried to obtain phosphorylated cellulose; The preparation method of the molybdenum disulfide nanosheets described in step S1 is as follows: The ammonium paramolybdate, thiourea and surfactant are uniformly mixed in a mass ratio of (5-10): (2.5-5): 1, reacted at 200-240°C for 20-24 hours, and molybdenum disulfide nanosheets are obtained after impurity removal and drying.
2. The method for preparing the phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material according to claim 1, characterized in that: The mass content of phosphorylated cellulose in the mixture in step S1 is 2-5%.
3. The method for preparing the phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material according to claim 1, characterized in that: The mass ratio of the phosphorylated cellulose, the molybdenum disulfide nanosheets and the polyethyleneimine is (1-3): (1-2): (2-4).
4. The method for preparing the phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material according to claim 1, characterized in that: In step S1, the ionic liquid includes one of 1-allyl-3-methylimidazolium chloride and 1-butyl-3-methylimidazolium chloride.
5. The method for preparing the phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material according to claim 1, characterized in that: The surfactant includes one of polyvinyl pyrrolidone and hexadecyl trimethyl ammonium bromide.
6. A phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material prepared by the preparation method according to any one of claims 1 to 5.
7. Use of the phosphorylated microcrystalline cellulose-modified molybdenum disulfide aerogel material according to claim 6 in the adsorption of dye wastewater.
8. The use according to claim 7, characterized in that The dye wastewater is methyl orange wastewater.
Citation Information
Patent Citations
Halogen-free cellulose based phosphorus flame retardant and preparation method thereof
CN104356242A
Preparation method of functional nano-cellulose composite aerogel
CN107556495A